2022
DOI: 10.3390/app12105154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light Reflection from the Wall and Ceiling Due to Color Changes in the Indoor Environment of the Selected Hall

Abstract: The main goal of this paper is to evaluate the effect of color changes on the interior surfaces of a selected hall on the level of daylight, represented by the DF factor. A single-story hall was chosen as the reference building, in which daylight falls through the side windows and a skylight at roof level. Measurement of the level of daylight in the real state of the building (in situ) was carried out. The measurement took place when the external boundary conditions of the measurement were met (external state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Differences in reflectivity and colour are essential design elements within modern buildings because they provide vital contrast. Colour also influences the subjective visual perception of light, and is associated with psychological, physiological, and social reactions [79]. In architecture, Light Reflectance Values are a measure of the percentage of visible and usable light that is reflected from a surface when illuminated by a light source [80].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in reflectivity and colour are essential design elements within modern buildings because they provide vital contrast. Colour also influences the subjective visual perception of light, and is associated with psychological, physiological, and social reactions [79]. In architecture, Light Reflectance Values are a measure of the percentage of visible and usable light that is reflected from a surface when illuminated by a light source [80].…”
Section: Resultsmentioning
confidence: 99%
“…(p.13) Surface color reflectance must also be taken into consideration (Elqahtani & Egzawi, 2015), as this can play a critical role in lighting efficiency, workplace productivity, and visual comfort of all users of the space. For example, studies have shown that a ceiling with a reflectance of 0.89 compared to 0.75 may increase "light levels by 25% with indirect lighting, 18% with direct/ indirect lighting, and up to 4% with direct lighting," with most studies showing this effect with very light-colored or white walls (Katunsky ´et al, 2022). While the sole use of white on both wall and ceiling surfaces in healthcare environments has been shown to have negative effects on patients, white can be used on ceilings and in rooms where high reflection of light is needed or preferred (Brawley, 1997).…”
Section: Relationship Between Lighting and Color In Nicusmentioning
confidence: 99%
“…The determination of the current state of architectural color is both a respect for the natural characteristics of the city and regional culture, and a basic way to analyze the current problem, which is directly related to the renewal and renovation of architecture as well as new construction [ 2 ]. Color in the interior of buildings has also been studied by some scholars [ 3 ]. Although the urban space architectural color measurement has achieved some success in recent years, but limited by the longtime of architectural color data collection, excessive human and material resources consumption and other limitations, the mainstream color measurement method is still mainly quantitative research, but also part of the quantitative research using a combination of local architectural color sampling and expert interviews [ 4 ].…”
Section: Introductionmentioning
confidence: 99%